2022
DOI: 10.3389/fbioe.2022.1000879
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory priming with IL-1β promotes the immunomodulatory behavior of adipose derived stem cells

Abstract: Inflammatory processes contribute to osteoarthritis (OA) severity and progression. Mesenchymal stem cells, particularly those derived from adipose tissue (ASCs), are able to sense and control the inflammatory environment. This immunomodulatory potential can be boosted by different priming strategies based on inflammatory stimulation. The aim of the present study is to investigate the transcriptional modulation of a huge panel of genes and functionally verify the predicted immunomodulatory ability of ASCs after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The immunomodulatory capacity of MSCs and ASCs can be influenced by disease status of the joint as noted by the groups of G. J. V. M. van Osch* and of G. Lisignoli* (Leijs et al, 2012;Manferdini et al, 2020). The immunomodulatory ability of ASCs was not affected by hypoxia as reported by the group of G. J. V. M. van Osch* (Roemeling-van Rhijn et al, 2013), whereas it was positively affected by an inflammatory stimulus such as interleukin 1 beta (IL-1β) as observed by the groups of L. de Girolamo* and of D. Noël* (Colombini et al, 2022b;Maumus et al, 2016). Similarly, the protein cargo of umbilical cord EVs was affected by their pro-inflammatory priming, but not in hypoxic conditions (Hyland et al, 2020).…”
Section: Differentiation and Culture Conditions For Appropriate Msk D...mentioning
confidence: 84%
“…The immunomodulatory capacity of MSCs and ASCs can be influenced by disease status of the joint as noted by the groups of G. J. V. M. van Osch* and of G. Lisignoli* (Leijs et al, 2012;Manferdini et al, 2020). The immunomodulatory ability of ASCs was not affected by hypoxia as reported by the group of G. J. V. M. van Osch* (Roemeling-van Rhijn et al, 2013), whereas it was positively affected by an inflammatory stimulus such as interleukin 1 beta (IL-1β) as observed by the groups of L. de Girolamo* and of D. Noël* (Colombini et al, 2022b;Maumus et al, 2016). Similarly, the protein cargo of umbilical cord EVs was affected by their pro-inflammatory priming, but not in hypoxic conditions (Hyland et al, 2020).…”
Section: Differentiation and Culture Conditions For Appropriate Msk D...mentioning
confidence: 84%
“…Most HUC-MSCs were dead and then quickly phagocytosed by monocytes after 24 h. Cocultured studies of MSCs either using a transwell or directly with two kinds of NK cell lines demonstrated that granule polarization is either induced or restrained through the special crosstalk of MSCs on the two NK cell lines [ 97 ]. Moreover, some studies found that AMSCs can switch an activated-M1 pro-inflammatory phenotype of macrophages to its anti-inflammatory M2 phenotype associated with the specific function of prostaglandin E2 (PGE2) [ 98 , 99 ]. Furthermore, MSCs hold substantial therapeutic promise to prevent unrestrained neutrophil activation-induced tissue damage depending on the neutrophils’ engulfment of intercellular adhesion molecule-1 (IAM-1) derived from MSCs [ 100 , 101 ].…”
Section: Immunomodulation Of Mscsmentioning
confidence: 99%
“…Regarding treatment with IL-1β, priming of hASCs from patients with osteoarthritis (OA) with this cytokine (1 ng/ml for 24 h) induced the differential expression of genes enriched in inflammation modulation and extracellular matrix (ECM) remodeling. Moreover, compared to non-primed cells, IL-1β primed hASCs superiorly modulated the CD80 + /CD206 + cell ratio in co-culture with polarized M1 macrophages, promoting an increase of the anti-inflammatory CD206 + M2a macrophages [ 112 ].…”
Section: Asc Priming/licensing/preconditioningmentioning
confidence: 99%
“…The impact of inflammatory diseases on the immunosuppressive properties of hASCs has been extensively investigated to include RD [ 46 , 47 , 96 , 112 , 231 , 247 257 ], T2D [ 67 , 109 , 156 , 258 ], sepsis [ 259 ], Crohn’s disease [ 260 263 ], ulcerative colitis [ 264 ], breast cancer [ 265 – 269 ], osteoporosis [ 270 ], psoriasis vulgaris [ 140 ], Parkinson's disease [ 271 ], and atherosclerosis [ 272 ]. The results are contradictory from diseased ASCs having intact immunomodulatory functions to impaired immunosuppressive effects.…”
Section: Donor-related Parametersmentioning
confidence: 99%
See 1 more Smart Citation